1980
DOI: 10.7326/0003-4819-92-1-53
|View full text |Cite
|
Sign up to set email alerts
|

"Pittsburgh Pneumonia Agent": A Bacterium Phenotypically Similar to Legionella pneumophila and Identical to the TATLOCK Bacterium

Abstract: The "Pittsburgh pneumonia agent," isolated by Pasculle and co-workers from human lung tissue, has been cultured on artificial media and characterized. The "Pittsburgh" bacterium and the TATLOCK and HEBA bacteria have identical cultural, biochemical, and antigenic characteristics. They also have the same cellular fatty-acid composition, and DNA relatedness indicates that they belong to the same species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
20
0

Year Published

1980
1980
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(22 citation statements)
references
References 12 publications
2
20
0
Order By: Relevance
“…From tissues, Tatlockia may be partly acid-fast (20). Although motility of some strains has been reported (10) and polar flagella have been demonstrated (10,12,20), these organisms are usually nonmotile after agar passage. Motility of some strains may be restored by passage on semisolid media.…”
Section: Resultsmentioning
confidence: 99%
“…From tissues, Tatlockia may be partly acid-fast (20). Although motility of some strains has been reported (10) and polar flagella have been demonstrated (10,12,20), these organisms are usually nonmotile after agar passage. Motility of some strains may be restored by passage on semisolid media.…”
Section: Resultsmentioning
confidence: 99%
“…Since the discovery of Legionella pneumophila, the agent of Legionnaires disease, two other groups of fastidious bacteria have been isolated (1,7,9,13,19,21,22) which share some phenotypic characteristics with L. pneumophila (6,7,11,13). However, deoxyribonucleic acid (DNA) hybridization studies demonstrated no sigrzlficant homology between these strains and L. pneumophila (5, 8-10, 13-15, 18), thereby excluding relatedness at the genus level.…”
mentioning
confidence: 99%
“…However, deoxyribonucleic acid (DNA) hybridization studies demonstrated no sigrzlficant homology between these strains and L. pneumophila (5, 8-10, 13-15, 18), thereby excluding relatedness at the genus level. One group contains the strains known as the Pittsburgh pneumonia agent (PPA) (11,19) and the TATLOCK strain (9, 11, Z l ) , for which three scientific names, Legionella micdadei, L. pittsburghensis (18), and Tatlockia micdadei (8), have been proposed. Members of the second group are serologically more diverse (7,13) and have been referred to as atypical Legionella-like organisms (ALLO) (7).…”
mentioning
confidence: 99%
“…This organism has now been cultivated on artificial media and shown to be phenotypically similar to, but genetically and antigenically distinct from, Legionella pneumophila (13,18). The names Legionella micdadei (12) and Legionellapittsburgensis (18) have been proposed for this organisim and two similar isolates, TAT-LOCK and HEBA (11).…”
mentioning
confidence: 99%
“…Analysis of the antibiotic therapy given patients in the clusters of L. micdadei pneumonia which occurred in Pittsburgh, Pa., and Charlottesville, Va., did not reveal any pattern of antimicrobial efficacy (17,20). However, many of these patients received beta-lactam and aminoglycoside antibiotics, both alone and in combination, to which L. micdadei displays marked in vitro susceptibility, and yet 8 of these 13 patients died. Susceptibility testing of L. micdadei with an egg protection model has shown that beta-lactam and aminoglycoside antibiotics are also not effective in ovo (17).…”
mentioning
confidence: 99%